Identification and management of poor response to growth-promoting therapy in children with short stature - Bang, Peter; Bettendorf, Markus (Clinical endocrinology, 2012)
Growth hormone (GH) is widely prescribed for children with short stature across a range of growth disorders. Recombinant human (rh) insulin-like growth factor-1 (rhIGF-1) therapy is approved for severe primary IGF-I deficiency - a state of severe GH resistance. Evidence is increasing for an unacceptably high rate of poor or unsatisfactory response to growth-promoting therapy (i.e. not leading to significant catch up growth) in terms of change in height standard deviation score (SDS) and height velocity (HV) in many approved indications. Consequently, there is a need to define poor response and to prevent or correct it by optimizing treatment regimens within accepted guidelines. Recognition of a poor response is an indication for action by the treating physician, either to modify the therapy or to review the primary diagnosis leading either to discontinuation or change of therapy. This review discusses the optimal investigation of the child who is a candidate for GH or IGF-1 therapy so that a diagnosis-based choice of therapy and dosage can be made. The relevant parameters in the evaluation of growth response are described together with the definitions of poor response. Prevention of poor response is addressed by discussion of strategy for first-year management with GH and IGF-1. Adherence to therapy is reviewed as is the recommended action following the identification of the poorly responding patient. The awareness, recognition and management of poor response to growth-promoting therapy will lead to better patient care, greater cost-effectiveness and increased opportunities for clinical benefit.
Gesehen am 27.09.2018